The essential hemingway - , Ernest Hemingway ([S.l.] : Arrow, 1994)
The Essential Hemingway is the perfect introduction to the astonishing, wide-ranging body of work by the Noble Prize-winning author. This impressive collection includes: the full text of Fiesta, Hemingway's first major novel; long extracts from three of his greatest works of friction, A Farewell to Arms, To Have and Have Not, and For Whom the Bell Tolls; twenty-five complete short stories; and the breathtaking Epilogue to Deathin the Afternoon.
Import.